Energy utilization by sheep and buffalo from a roughage ration at maintenance level of feeding - Murarilal, Murarilal; Khan, M Y; Haque, N (The Indian Journal of Animal Sciences, 2012)
Adult male Murrah buffaloes (4) weighing 350 kg, and 6 rams of 13 kg were fed on oat green and wheat straw in the same ratio for their maintenance. Energy distribution was determined in an open circuit respiration chamber. The dry matter intakes of 65.5 and 58.6 g/kg Wâ°Ë™â·âµÌ‡/day in buffalo and sheep, respectively. were significantly (P<0.05) different from each other. The digestibility of DM, OM, CF and NFE was significantly (P<0.01) higher in sheep. The balance of nitrogen was positive in both the species. The intake of GE was 277.4 and 249.4 kcal/kg Wâ°Ë™â·âµÌ‡/day in buffalo and sheep respectively. The intake of GE in buffalo was significantly (P<0.05) higher than in sheep. Significantly (P<0.05) higher loss of energy through faeces in buffalo resulted ill similar level of DE intake in both the species. The ME intake per kg metabolic body size per day was similar in both the species. Significant (P<0.01) increase in metabolizability and digestibility of gross energy of the diet increased significantly (P<0.01) in sheep than that in buffalo. It is concluded that ME value of all roughage ration determined with sheep was an over estimation for buffalo.